Characterization and delineation of two infraspecific taxa of Dioscorea esculenta (Lour.) Burkill: The leaf architecture approach (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Antonio MA, Buot Jr. IE. 2021. Characterization and delineation of two infraspecific taxa of Dioscorea esculenta (Lour.) Burkill: The leaf architecture approach. Biodiversitas 22: 1783-1789. The current taxonomic treatment for the wild and cultivated species of Dioscorea esculenta Lour. (Burkill) presented them as two different varieties. However, there are confusions among botanists and farmers. So, leaf architecture analysis was done to investigate whether leaf architecture data would support their current taxonomic treatment. The varieties showed variability in several characteristics indicating their distinct identity from each other. Based on general leaf characters, they differ in all the parameters observed. But on venation characters, evident variation was seen only on the number of basal veins and secondary vein angle of divergence. Nevertheless, the two varieties resemble each other in a number of characters, i.e. campylodromous primary veins, brochidodromous secondary veins, presence of intermarginal and intersecondary veins, admedially ramified tertiary veins, and well-developed areolation. Dendrogram generated from cluster analysis agrees with and supports above leaf architectural examination, suggesting the two varieties to be recognized as separate taxa. But the current taxonomic treatment naming them as var. spinosa and var. fasciculata seemed to have dragged the cultivated plant into the classification system generally used for wild plants. Thus, the proposed name for the cultivated plant is D. esculenta ‘fasciculata’ while that of the wild plant remains as D. esculenta var. spinosa.
Keywords: Dioscorea esculenta Dioscorea esculenta ‘fasciculata’, Dioscorea esculenta var. spinosa, leaf anatomy Leaf architecture